Rethinking Energy-Performance Trade-Off in Mobile Web Page Loading - Bui, Duc Hoang; Liu, Yunxin; Kim, Hyosu; Shin, Insik; Zhao, Feng (The 21st Annual International Conference on Mobile Computing and Networking (MobiCom 2015), 2015)
Web browsing is a key application on mobile devices. However, mobile browsers are largely optimized for performance, imposing a significant burden on power-hungry mobile devices. In this work, we aim to reduce the energy consumed to load web pages on smartphones, preferably without increasing page load time and compromising user experience. To this end, we first study the internals of web page loading on smartphones and identify its energyinefficient behaviors. Based on our findings, we then derive general design principles for energy-efficient web page loading, and apply these principles to the open-source Chromium browser and implement our techniques on commercial smartphones. Experimental results show that our techniques are able to achieve a 24.4% average system energy saving for Chromium on a latest-generation big.LITTLE smartphone using WiFi (a 22.5% saving when using 3G), while not increasing average page load time. We also show that our proposed techniques can bring a 10.5% system energy saving on average with a small 1.69% increase in page load time for mobile Firefox web browser. User study results indicate that such a small increase in page load time is hardly perceivable.